Computer skills, destination language proficiency and the earnings of natives and immigrants - Barry R. Chiswick; Paul W. Miller (Institute for the Study of Labor (IZA), 2005)
Using data from the 2001 Census of Population and Housing in Australia, this paper investigates the determinants, and consequences for earnings, of computer use by both the native born and the foreign born. Focussing on the foreign born, the multivariate analyses show that recent arrivals are more likely to use computers than the Australian born. As the level of computer use in Australia is much higher than in most of the countries that Australia's immigrants come from, this evidence suggests a high degree of favorable selection in migration. Study of the links between earnings, computer use and other human capital skills shows that educational attainment and destination language skills are complements to computer use. The use of a computer is shown to be a way the foreign born can increase the international transferability of their pre-immigration skills, a finding that has implications for immigrant settlement policies.
Keywords: F22; D13; J15; J24; J31; J61; 330; computers; internet; immigrants; language; earnings